Land-Use Effect on Olive Groves Pest Prays oleae and on Its Potential Biocontrol Agent Chrysoperla carnea - Alves, João Frederico (2021)
Olive growing has been intensified through the simplification of agricultural landscapes. In order to rethink the environmental drawbacks of these practices, conservation biological control techniques have been examined. In this work, Prays oleae and its natural enemy Chrysoperla carnea were monitored to account for the effects of the amount and diversity of different land-uses. We found that C. carnea showed an attraction to areas with high abundances of P. oleae but this predator did not display any affection by the different land-uses. Inversely, P. oleae abundance was lower in diverse landscapes and higher in simplified ones. Importantly, higher abundances of C. carnea were related to lower infestation levels of P. oleae in the late part of the season. These results corroborate the attraction of C. carnea to the olive moth, highlighting the potential of C. carnea as a biological control agent of this pest, assert that the promotion of land-use diversity can reduce P. oleae and confirm that landscapes dominated by olive groves can promote this pest. The present study aims at contributing to the discussion about the management of agricultural ecosystems by providing farmers with sustainable alternatives that do not have harmful effects on the environment and public health.